2023
DOI: 10.1002/bse.3327
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of blockchain technologies to anti‐corruption practices: A systematic literature review

Abstract: This paper proposes a systematic literature review emphasising scholars' view on the impact of the adoption of blockchain technologies to fight corruption. Providing a deep understanding of the state of the art, the paper drafts implications and valuable insights to address future research. The connection of anticorruption policies and blockchain technologies has been investigated using Scopus database and ABS journal ranking. The importance assumed by anticorruption policies and the innovativeness of the bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…better and more open processes, professional accountability systems, and innovative technologies to capture, analyse, and share data to prevent, detect, and deter corrupt behaviour (Trequattrini et al, 2022). In the business context, the fight against corruption could bring longterm benefits that far outweigh the costs of corruption phenomena, even if both benefits and costs are difficult to measure (Malanski and Pòvoa, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…better and more open processes, professional accountability systems, and innovative technologies to capture, analyse, and share data to prevent, detect, and deter corrupt behaviour (Trequattrini et al, 2022). In the business context, the fight against corruption could bring longterm benefits that far outweigh the costs of corruption phenomena, even if both benefits and costs are difficult to measure (Malanski and Pòvoa, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Blockchain technology finds widespread adoption across diverse sectors such as education, healthcare, and finance, showcasing its versatility and relevance [3]. Furthermore, blockchain technology's presence as a potent enabler fosters anticorruption efforts, adding another layer of societal significance [4]. In the financial sector, the rise of DeFi has proven instrumental, particularly within the crypto economic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Trequattrini et al (2022) analyse the contribution of blockchain‐based technologies to anticorruption practices. The blockchain is a distributed ledger technology (DLT) with an architecture that makes very complicated to perform corruption behaviour; therefore, anticorruption practices by organizations need to be investigated in the light of blockchain technologies adoption.…”
mentioning
confidence: 99%
“…The blockchain is a distributed ledger technology (DLT) with an architecture that makes very complicated to perform corruption behaviour; therefore, anticorruption practices by organizations need to be investigated in the light of blockchain technologies adoption. Therefore, Trequattrini et al (2022) critically review the literature on the impact of the adoption of blockchain technologies by organizations to fight corruption and adopt anticorruption practices. The SLR revealed that the impact of blockchain technologies in fighting corruption has been largely investigated through a conceptual approach with many papers adopting a qualitative approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation